Women fishers in Norway: few, but significant - Gerrard, Siri; Kleiber, Danika (Maritime Studies, 2019)
Professional fishing and fisheries quota systems can affect women and men differently, yet gender analysis of quota systems is rare. In this article, we use a feminist framing and a mixed methods approach to examine the long-term gendered effects of the introduction of the 1990 quota system in Norway. Using statistics from the National Fishery Registry and the Directorate of Fisheries, we found that the number of women and men registered as fishers has declined since 1990 (an overall decline of 59%). Over this period, men have consistently outnumbered women among registered fishers (2.7–3.2% women), among boat owners (2.23% women in 2017) and particularly among owners of larger boats (> 11 m), which can have multiple quotas (0.35% women in 2017). However, changes in the age and geographic location among women fishers reflect changes to fisheries overall, as well as highlighting the gender-blind entry barriers that disproportionately impact women. In addition, contextualising statistical data with participant interviews conducted in North Norway, especially in Finnmark, enables us to examine more closely why the gender gap remains. This mixed method approach also identifies changes women and men working in fisheries have undergone, while also addressing women fishers’ political efforts to improve gender equity in Norwegian fisheries. Our study contributes to a more nuanced understanding of Norwegian coastal fishing, and particularly women’s small but significant presence.